Analysis of the Effect of Inventory Turnover, Receivables Turnover and Leverage on Profitability Levels in Automotive Companies Listed on the Indonesian Stock Exchange - Husni Mubaarak; M. Syafii (International Journal of Economics Development Research (IJEDR), 2024)
Profitability is a ratio that measures ability company to pay all short-term financial obligations at maturity using available current assets. The research method used is a descriptive qualitative approach with descriptive and inferential analysis. The population of this research is automotive companies listed on the Indonesia Stock Exchange (BEI) in 2016-2020, with samples carried out using a purposive sampling method of 9 companies. The research results show that Leverage has a significant effect on Profitability Levels in automotive companies listed on the Indonesia Stock Exchange. This means that the higher the company's leverage ratio, the more impact it will have on the company's level of profitability. Inventory turnover has a significant effect on profitability levels in automotive companies listed on the Indonesia Stock Exchange. This also indicates that when inventory turnover increases or decreases, it will have an impact on the company's level of profitability. Receivables Turnover has a significant effect on Profitability Levels in automotive companies listed on the Indonesia Stock Exchange. This indicates that receivables turnover, whether large or small, will influence the company's level of profitability.